Klinične in histološke značilnosti ploščatoceličnega karcinoma kože - Soyer, Peter H. (Radiology and oncology (Ljubljana), 1999)
The spindle cell carcinoma is second commonest tumor of the skin. Chronic exposure to UV radiation appeares to be the most important aetiological factor. The clinical presentation shows great variability which causes problems to differentiate these tumors from other skin disease, especially thebasalioma. Histological and uncertain cases immunohistochemical exammination are required to make the final diagnosis.
Keywords: Carcinoma; Diagnosis; diagnostika; Immunohistochemistry; kožni rak; Pathology; rak (medicina); Skin neoplasms